Assessment of treated sewage effluent as an alternative clean water source for car wash applications - Hussin, Muhammad Gadaffi; Ariff, Nor Azliana; Rohani, Rosiah; Muhammad, Nur Shazwani; Jaafar, Othman; Mohammad Afandi, Syamsul Herman (National University of Malaysia, 2025)
Sewage treatment is a critical process for ensuring that wastewater is treated to meet regulatory discharge standards. However, further polishing of the treated effluent is often required for applications such as vehicle washing, where water quality must meet specific criteria to prevent harm to users and potential damage to vehicles. This study evaluates the quality of treated effluent from a dedicated Sewage Treatment Plant (STP) after undergoing various post-treatment processes. Key parameters for physical, chemical, and biological, were analyzed to assess the suitability of the polished water for vehicle washing, referencing national drinking water standards as a benchmark. Review showed that the quality of the treated water for the targeted application should meet the national water quality standards (NWQS) Class I at the minimum, however best practice to follow drinking water quality standards. The turbidity, biological oxygen demand (BOD), chemical oxygen demand (COD), Ammonia nitrogen, oil and grease as well as e-coli/total coliform are parameters that do not meet the requirements upon treatments other than reverse osmosis. It is also confirmed that the membrane-based treatments, particularly RO, significantly improve water quality compared to conventional biological processes. RO-treated water exhibited characteristics comparable to local potable tap water, with complete removal of bacterial contaminants, confirming its safety for direct contact applications. In conclusion, integrating advanced membrane technologies such as ultrafiltration (UF) and RO into STPs can produce high-quality effluent suitable for vehicle washing without adverse effects. Several samplings and water quality analyses of the RO treated water have verified the consistency of the water quality that meets the drinking water standards. This study could serve for sustainable development goal (SDG) specifically for SDG 6 on clean water and sanitation, which is essential in ensuring the availability and sustainable management of water and sanitation for all.